TRAUMA DAN FRAMING PERSEPSI DALAM TINJAUAN AL-QUR’AN (Analisis Kisah Bani Israil di Surah Al-Māidah dan Kisah Bani Musthaliq di Surah Al- Ḥujurāt) - Saiful Bahri (Universitas Ahmad Dahlan, 2021)
The trauma experienced by a person can result in a mental block that makes him locked in negative perceptions and difficult to let go. As well the perception of something if it is not perfect or wrong will result in harm to oneself and others. Al-Qur’an as hudan (guidance) and ṡifâ' (solution) certainly has attention and solutions to deal with these two mental conditions. This article discusses these two themes with a psychological and thematic approach. The cases analyzed are the perceptual trauma experienced by Bani Israel which is narrated in Surah al-Maidah, as well as the perception framing experienced by the messenger of the Prophet Muhammad to the Bani Musthaliq tribe which is narrated as the cause of the revelation of Surah al- Ḥujurāt verse six. This psychological solution based on the verses of the al-Qur’an is expected to be able to overcome and prevent these two psychological problems.